2015
DOI: 10.1021/acscatal.5b00330
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Activated Nanoporous Gold: A Stable and Storable Material for Catalytic Oxidation

Abstract: We report a new method for facile and reproducible activation of nanoporous gold (npAu) materials of different forms for the catalytic selective partial oxidation of alcohols under ambient pressure, steady flow conditions. This method, based on the surface cleaning of npAu ingots with ozone to remove carbon documented in ultrahigh vacuum conditions, produces active npAu catalysts from ingots, foils and shells by flowing an ozone/dioxygen mixture over the catalyst at 150 °C, followed by a temperature ramp from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(140 citation statements)
references
References 34 publications
(122 reference statements)
8
131
0
Order By: Relevance
“…[48,191] Reproducible catalyst activation of these np-Au catalysts is critical but can be achieved through an ozone treatment at atmospheric pressure. [192] Similar to the previously mentioned np-Pt, there are mass transport limitations due to the tortuous porosity of the material, which become more severe with decreasing pore size. [24] The importance of the material architecture is illustrated by the results of a recent study that evaluated the reactivity of np-Au catalysts in three different forms: ingots, foils, and hollow shells.…”
Section: Metal Catalystsmentioning
confidence: 75%
See 2 more Smart Citations
“…[48,191] Reproducible catalyst activation of these np-Au catalysts is critical but can be achieved through an ozone treatment at atmospheric pressure. [192] Similar to the previously mentioned np-Pt, there are mass transport limitations due to the tortuous porosity of the material, which become more severe with decreasing pore size. [24] The importance of the material architecture is illustrated by the results of a recent study that evaluated the reactivity of np-Au catalysts in three different forms: ingots, foils, and hollow shells.…”
Section: Metal Catalystsmentioning
confidence: 75%
“…[24] The importance of the material architecture is illustrated by the results of a recent study that evaluated the reactivity of np-Au catalysts in three different forms: ingots, foils, and hollow shells. [192] The study revealed that the conversion rates of methanol to methylformate are five times higher for the hollow shell and foil morphology when compared to the ingot. [192] The higher conversion rates for foils and porous shells reveal that these morphologies can mitigate the mass transport limitations that are inherent to non-hierarchical bulk np materials.…”
Section: Metal Catalystsmentioning
confidence: 96%
See 1 more Smart Citation
“…The current research in gold catalysis consists of the study of catalytic reactions on nanoporous catalysts [261][262][263][264][265]. The nanoporous Au, npAu, consists of a 3D structure of interconnected pores and ligaments with a ligament size in the 20-100 nm range.…”
Section: Processes On Self-supported Aumentioning
confidence: 99%
“…In this work, the authors focused on influence of ozone activation on the catalyst to improve the selectivity towards alcohol oxidation reactions. One of the key steps towards this goal is the dissociation of oxygen species at the surface of the catalyst, and Ag provides active sites for oxygen dissociation [261][262][263][264][265].…”
Section: Nanoporous Au As Catalyst For Selective Alcohol Oxidationmentioning
confidence: 99%